Women in Positive Peacebuilding: Urgent Demands for Overcoming the Socio-Environmental and Armed Conflict in Colombia - Serrano Marlés, Daniela Catalina (2026)
This research article analyzes the role of women in positive peacebuilding to overcome the socio-environmental and armed conflict in Colombia. It uses a holistic approach, primarily influenced by the constructivist paradigm, to develop an analytical methodology with a documentary, evolutionary, and multivariate design. The methodology consisted of reviewing a series of official documents from an ecofeminist perspective. The goal was to reveal challenges, achievements, and developments in the government approaches adopted for peacebuilding following the signing of the Havana Agreement between the Colombian government and the FARC-EP subversive group. The results show that, while discursive advances have been incorporated around gender equity and the recognition of nature as a subject of rights, multiple gaps persist in the territorial implementation of policies, especially in contexts where women have traditionally been excluded. Furthermore, a persistent instrumentalization of the female role is observed in post-agreement scenarios, which limits their transformative participation. The research concludes that a truly sustainable and just peace in Colombia requires the active integration of women as political and environmental agents, going beyond welfare-based approaches, by strengthening community leadership, protecting women environmental defenders, and adopting a cross-cutting ecofeminist perspective in state planning.